The Era of 1-bit LLMs: All Large Language Models are in 1.58 Bits - Ma, Shuming; Wang, Hongyu; Ma, Lingxiao; Wang, Lei; Wang, Wenhui; Huang, Shaohan; Dong, Lifeng; Wang, Ruiping; Xue, Jilong; Wei, Furu (arXiv, 2024)
Recent research, such as BitNet, is paving the way for a new era of 1-bit Large Language Models (LLMs). In this work, we introduce a 1-bit LLM variant, namely BitNet b1.58, in which every single parameter (or weight) of the LLM is ternary [-1, 0, 1]. It matches the full-precision (i.e., FP16 or BF16) Transformer LLM with the same model size and training tokens in terms of both perplexity and end-task performance, while being significantly more cost-effective in terms of latency, memory, throughput, and energy consumption. More profoundly, the 1.58-bit LLM defines a new scaling law and recipe for training new generations of LLMs that are both high-performance and cost-effective. Furthermore, it enables a new computation paradigm and opens the door for designing specific hardware optimized for 1-bit LLMs.
Work in progress